EKSPLORASI DILEMA INDEPENDENSI: STUDI FENOMENOLOGI AUDITOR INTERNAL PERGURUAN TINGGI - Faris Afrizal; Wuri Handayani (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
This study aims to explore the perception of independence among internal auditors, describe the auditor's experience with independence dilemmas, and how auditors deal with these dilemmas. This research adopts a phenomenological study to reveal the experience of internal auditors when encountering independence dilemmas. This study conducted interviews with four internal auditors in the one of prominent higher education institutions in Indonesia. The result of this study demonstrates that internal auditors experience role conflicts that arise from an independence dilemma felt by internal auditors. Consequently, the internal auditor attempts to manage the role conflict by adopting coping tactics that can minimize the occurrence of role conflict. The role theory and coping strategies are employed to understand how internal auditors experience a role conflict and how the auditor handles such conflict.